QUALITY OF LIFE IN GLAUCOMA KVALITET ŽIVOTA KOD GLAUKOMA - Senćanić, Ivan; Grgurević, Anita; Jakšić, Vesna (Medicinski podmladak, 2019)
Abstract Glaucoma is a progressive neurodegenerative disease that can lead to irreversible blindness, if left untreated. There are different modalities in glaucoma treatment, but the most common include using local hypotensive eye drops. Due to the visual impairment or the use of glaucoma medication, people with glaucoma often report different difficulties in everyday life. Simple exams and assessments of clinical glaucoma parameters (like visual field) are not sufficient to describe patients’ problems and needs. Therefore, the investigation of their quality of life (QOL) is indispensable in management of glaucoma patients. Quality of life in people with glaucoma is usually decreased and typically physical, psychological and social aspects are affected. Quality of life is usually evaluated with the use of patient reported outcome measures (PRO) and the most used form of PRO is questionnaire. Recently, two of the glaucoma specific questionnaires - Glaucoma Quality of life-15 and Glaucoma Symptom Scale – have been validated in the Serbian language and are available for use in glaucoma populations. The main goal of glaucoma management should be preserving patients’ vision while keeping and improving their quality of life, which is the reason why QOL assessments are of a great importance in glaucoma. Keywords: glaucoma, quality of life, glaucoma specific questionnaires Sažetak Glaukom je progresivno neurodegenerativno oboljenje koje, ukoliko se ne leči, može da dovede do potpunog slepila. Postoje različiti terapijski pristupi u lečenju glaukoma, pri čemu je najčešći oblik terapije primena lokalne hipotenzivne terapije u vidu kapi. Osobe sa glaukomom često navode različite probleme u svakodnevnom funkcionisanju. Osnovni pregled i procena kliničkih parametara vezanih za glaukom (npr. vidno polje) ne mogu u potpunosti da opišu sve poteškoće i potrebe sa kojima se suočavaju osobe sa glaukomom. Stoga je procena kvaliteta života nezaobilazna stavka u praćenju osoba obolelih od ove bolesti. Kvalitet života kod ovih osoba obično je narušen i to posebno njegovi fizički, psihološki i socijalni aspekti. Procena kvaliteta života se obično vrši uz pomoć merila pacijentovog prikaza ishoda (engl. patient reported outcome measures). Najčešći oblik merila su upitnici. Dva upitnika za glaukom su validirana i dostupna na srpskom jeziku: Kvalitet života kod glaukoma 15 (engl. Glaucoma Quality of life-15) i Skala simptoma kod glaukoma (engl. Glaucoma Symptom Scale). Ispitivanje kvaliteta života kod glaukoma od velike je važnosti budući da glavni princip lečenja ovih osoba predstavlja očuvanje postojećeg vida, uz održavanje i poboljšanje njihovog kvaliteta života. Ključne reči: glaukom, kvalitet života, glaukom specifični upitnici